Ethnomedicinal Practices and Traditional Medicinal Plants of Barak Valley, Assam: a systematic review - Pervej Alom Barbhuiya; Abdul Mannaf Laskar; Hemanga Mazumdar; Partha Pratim Dutta; Manash Pratim Pathak; Biplab Kumar Dey; Saikat Sen (Journal of Pharmacopuncture, 2022)
Objectives: The Barak Valley is well known for its rich diversity of medicinal plants. Ethnomedicinal practices are prominent among Barak Valley’s major and minor ethnic groups. This systemic review focuses on traditionally used medicinal plants found in the Barak Valley as reported in different ethnobotanical surveys.Methods : We searched various databases, including PubMed, Web of Science, and Google Scholar, to find ethnomedicinal surveys conducted in the Barak Valley. The search was performed using different terms, including ethnomedicinal survey, folk medicine, indigenous knowledge, and Barak Valley. Potential articles were identified following the exclusion and inclusion criteria.Results : A total of eight ethnobotanical surveys were included in this study. We identified a total of 216 plant species belonging to 167 genera and 87 families, which are widely used by the ethnic communities who live in the rural areas of Barak Valley for the treatment of various diseases and ailments.Conclusion : Folk medicine is the result of decades of accumulated knowledge and practices by people who live in rural communities based on their needs and provides an important source of information to assist the search for new pharmaceuticals. Therefore, available information on traditional medicinal plants needs to be explored scientifically to find effective and alternative treatments for different diseases.